Biological and phytochemical review on the genus Coccoloba (Polygonaceae) - Fatma Abdel Hakim; Haidy A. Gad; Rasha Ali Radwan; Nahla Ayoub; Mohamed El-Shazly (Ain Shams University, 2019)
Polygonaceae is one of the largest medicinal plant families, vastly distributed worldwide, containing around 1,200 species from 48 genera. Most of the species are located in the northern temperate region, while the other species are allocated from the tropics to the arctic. The prime genera in Polygonaceae are Eriogonum which includes 240 species, Rumex with 200 species, Coccoloba with 120 species, Persicaria with 100 species, and Calligonum with 80 species. Coccoloba is one of the most interesting genera of the family Polygonaceae in terms of biological activities and secondary metabolites. Plants of this genus are used worldwide in traditional folk medicine. The review is a comprehensive literature survey on different Coccoloba species regarding their biological activities and their isolated phytochemicals. Different classes of secondary metabolites were isolated from this genus including flavonoids, phenolic acids, tannins, triterpenes, diterpenes, anthraquinones, isochromene, and volatile oils. Crude extracts and isolated compounds of various Coccoloba species displayed diversity in biological activities. Further investigations are required to explore new bioactive compounds and their pharmacological activities.